This is the star - Dunbar, Joyce; Blythe, Gary (San Diego : Harcourt Brace, 1996)
A cumulative presentation which uses rhyme to describe the night of the birth of Christ.
Keywords: Jesus Christ -- Nativity -- Juvenile literature; Jesus Christ -- Nativity; Christmas